2014
DOI: 10.1177/0956462413518762
|View full text |Cite
|
Sign up to set email alerts
|

High HIV prevalence among children presenting for general consultation in rural Cameroon

Abstract: Data on the HIV-prevalence children presenting to health care facilities in sub-Saharan Africa are scant in general, and the debate about opportunities for paediatric HIV screening is ongoing. Nine hundred and eighty-one children with unknown HIV-status presenting to a large general paediatric outpatient department in rural Cameroon were tested using the Determine HIV-1/2 rapid test (Abbott), and positive results were confirmed with the Hexagon HIV rapid test (Human Diagnostics). In children younger than 18 mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 7 publications
1
11
1
Order By: Relevance
“…The HIV prevalence (4.3%) in the general population in Cameroon (4.3%) [ 17 ] is lower compared to Malawi (9.2%) and Kenya (5.4%) [ 8 ] and this may explain the lower HIV positivity rate observed among the pediatric and adolescent population in our study compared to Malawi and Kenya as reported in the aforementioned studies. In the bPITC group, we found a prevalence of 1.6%, which was similar to the 1.8% reported by Zoufaly et al in rural Cameroon [ 18 ] and closer to the 2.7% reported by Cohn et al in a meta-analysis [ 19 ].…”
Section: Discussionsupporting
confidence: 89%
“…The HIV prevalence (4.3%) in the general population in Cameroon (4.3%) [ 17 ] is lower compared to Malawi (9.2%) and Kenya (5.4%) [ 8 ] and this may explain the lower HIV positivity rate observed among the pediatric and adolescent population in our study compared to Malawi and Kenya as reported in the aforementioned studies. In the bPITC group, we found a prevalence of 1.6%, which was similar to the 1.8% reported by Zoufaly et al in rural Cameroon [ 18 ] and closer to the 2.7% reported by Cohn et al in a meta-analysis [ 19 ].…”
Section: Discussionsupporting
confidence: 89%
“…7 Paediatric inpatient programmes were the most common context (17), 6,7,10,[13][14][15][16][17][18][19][21][22][23][24][25]29,30 followed by nutrition centres (four), 9,11,12,27 EPI centres (three), 20 programmes (three). 8,20,31 The assessment for quality showed that most of the included studies (20) [9][10][11][12][15][16][17][18][19][20][22][23][24][25][26][27][28][29][30][31] were of fair or good quality and the remainder (six) [6][7][8]13,…”
Section: Resultsmentioning
confidence: 99%
“…9,23,28,31 Paediatric HIV prevalence across contexts in southern and eastern Africa was 17·8% (95% CI 12·8-22·7) and prevalence in west and central Africa was 9·8% (95% CI 4·2-15·3). Because of the small numbers of studies from Asia and Oceania, these geographical settings were not included in stratifi ed analyses.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While previous studies provided clues to the highest impact entry points for identifying HIV‐positive infants , these findings present the first evidence of differences in HIV prevalence amongst children accessing care at different health facility entry points in a low resource, generalized HIV epidemic. These data demonstrate high HIV prevalence among infants presenting for care at nutrition, inpatient, and PMTCT entry points.…”
Section: Discussionmentioning
confidence: 69%